The impact of teen intimate partner violence on subsequent new dating experiences among Latinas - Stubbs, Lucia J. (Marquette University, 2016)
Intimate Partner Violence (IPV) is experienced by Latinas (Villavicencio, 2008; González-Guarda, Peragallo, Vasquez, Urrutia, & Mitrani, 2009) at comparable and higher rates to women of other racial/ethnic backgrounds (Black et al., 2011; Centers for Disease Control and Prevention (CDC), 2011). Young Latinas, in particular, appear to be disproportionately affected by IPV in comparison to young non-Latina white women (CDC, 2011). The negative outcomes associated with IPV in women, including Latinas, range from physical health issues (e.g., death, injuries including broken bones and concussions), and illnesses (e.g., gastrointestinal issues, headaches, and cardiovascular problems), to mental health problems (e.g., depression, anxiety, and negative interpersonal relationship patterns) (Caetano & Cunradi, 2003; Krishnan, Hilbert, & VanLeeuwen, 2001; Brown et al., 2003). Despite these negative outcomes, women do engage in and navigate new relationships. It is unknown, however, how they approach these subsequent dating experiences. Understanding dating/relationships among Latinas following adolescent IPV is particularly important as the literature indicates adolescence marks a critical time for the initial development of interpersonal romantic relationship behaviors and dynamics, which can form lasting patterns (Makepeace, 1986; Lerner & Galambos, 1998; Glass, 2003). The purpose of the present study, therefore, was to explore how adolescent IPV influences subsequent, new dating experiences among Latinas. Grounded theory research methodology (Corbin & Strauss, 2008) was utilized to examine this topic. Eleven adult Latinas participated in interviews during which they were asked to discuss their dating, partner, and relationship expectations and behaviors subsequent to adolescent IPV. Results revealed that Latinas who experienced adolescent IPV underwent changes that led to an increased focus on self-protection, which was incorporated into subsequent partner/relationship expectations (e.g., less traditional gender roles, which also influenced other expectations including partnership; emotional support/space; self-expression/communication), relationship goals (e.g., a desire for an IPV-free relationship; monogamy; companionship) and new behaviors in dating/relationships (e.g., period of being single; cautious, slower approach to dating/relationships). Additionally, results indicated that most of the participants had entered subsequent satisfying, IPV-free relationships. Discussion of the findings, implications, and limitations of the present study are included. Directions for future research are also provided.